The Determination of Cognitive Structure of Candidate Teachers About Energy Centrals - Karatekin, Kadir; Topçu, Ersi̇n; Aydınlı, Bahattin (International Electronic Journal of Environmental Education, 2016)
Energy is the vital essence of every biotic and abiotic process. Energy is also in central position in human civilization. The famous energy centrals are the major way for production of energy with many diverse effects on environment. Therefore the mitigation of these effects is extremely important and one of its way is education in this controversial issue. The aim of this study is to investigate the cognitive structure of these candidate teachers with various branches towards energy centrals or power plants in the road of the solution of the environmental problem. They were asked to fill the word association test containing four major concepts, nuclear, hydroelectric, thermal and wind centrals. In sum, the nuclear central and wind central are found to be the most and the least dangerous ones sequentially in cognitive structure.
Keywords: Candidate teacher; word association test; energy centrals; cognitive structure; 13. Climate action; 7. Clean energy